New insects feeding on dinosaur feathers in mid-Cretaceous amber - Taiping Gao (Nature Portfolio, 2019)
Numerous feathered dinosaurs and early birds have been discovered from the Jurassic and Cretaceous, but the early evolution of feather-feeding insects is not clear. Here, Gao et al. describe a new family of ectoparasitic insects from 10 specimens found associated with feathers in mid-Cretaceous amber.